ANALYSIS OF THE STRATEGY FOR DEVELOPING THE POTENTIAL OF COMMUNITY-BASED ECOTOURISM (COMMUNITY BASED TOURISM) IN GULA LEMPENG CRAFTSMEN IN LASIANA VILLAGE, KUPANG CITY - Bessie, Juita Lubrina Domina; Kasim, Abas; Andriyani, Struce (Universitas Nusa Cendana, 2025)
The process of making Lempeng sugar is still traditional and is an activity that has been passed down from generation to generation by previous ancestors. Unfortunately, palm sugar production is decreasing because palm sap collectors and palm sugar makers have left the industry. The population of the Lontar tree is also endangered; the tree is often cut down for building materials, household furniture, and other art/cultural items, while the Lontar tree takes more than 12 years to be tapped. This study aims to identify internal and external factors of community-based ecotourism potential in Lempeng Sugar craftsmen in Lasiana Village, Kupang City in order to develop appropriate development strategies. This research is a quantitative descriptive research using SWOT. The data collection methods used are observation, interview and questionnaire distribution. Respondents in this study were 30 people. The sampling technique for respondents of the surrounding community and craftsmen was carried out with purposive sampling technique while the visitor respondents used accidental sampling technique. The results showed that Lempeng Sugar craftsmen in Lasiana Village have great potential for community-based ecotourism development. The main strengths lie in the diversity of cultural and natural tourism, local wisdom that is still maintained, and the strategic location near Lasiana Beach. Weaknesses that need to be overcome include an undirected tourism mindset, the decreasing number of craftsmen, and the quality of human resources that still needs to be improved. Opportunities that can be utilized include the increasingly popular trend of community-based tourism, government support, and technological developments for digital promotion. Threats that need to be anticipated include competition with other tourist destinations, negative impacts of tourism on the environment and local culture, and global economic instability. Keywords: Ecotourism; Gula Lempeng; SWOT; Community Based Tourism (CBT)